Mempelajari Wilayah Perbatasan Sebagai Ruang Bersama - Wahyuni Kartikasari (Jurnal Hubungan Internasional, 2013)
Border problems are often originated from a very complex issue. Problems that arise are because of there is no uncertainty about the border, and disparity of boundary zone development between the country and neighboring countries. The latter problem often encourages the orientation and mobility of border communities who tend to prefer to more rapid development area. Problems can arise from the differences perception and outlook between the government and society about the meaning of border, as well.This paper proposed the concept of shared space as a strategic move to overcome that perceptual difference on the border. A space that is managed together both in planning and implementation, will be able to minimize the number of conflicts and tensions that often arise in the border region.